Intranasal delivery of zidovudine by PLA and PLA-PEG blend nanoparticles - Mainardes, Rubiana Mara; Khalil, Najeh Maissar; Gremião, Maria Palmira Daflon [UNESP] (Elsevier B.V., 2010)
This study describes the preparation and evaluation of biodegradable poly(L-lactide) (PLA) and poly(L, lactide)-poly(ethylene glycol) (PLA-PEG) blend nanoparticles containing zidovudine as model drug. The prepared nanoparticles were characterized in terms of size, zeta potential, morphology and drug entrapment efficiency. The pharmacokinetics of zidovudine following intranasal administration in mice was assessed. The results showed that although PLA and blend nanoparticles had the same morphology, the particle size and zeta potential were changed by the PEG. The drug entrapment efficiency was increased by PEG presence. The pharmacokinetic study showed that all the nanoparticles were able to sustain zidovudine delivery over time, but greater efficiency was obtained with PLA-PEG blend nanoparticles, whose T(max) was twice that of PLA nanoparticles. The PLA and PLA-PEG nanoparticles formulations increased the zidovudine mean half-life by approximately 5.5 and 7 h, respectively, compared to zidovudine aqueous solution. The relative bioavailability of zidovudine-loaded PLA-PEG blend nanoparticles was 2.7, relative to zidovudine-loaded PLA nanoparticles and 1.3 relative to aqueous solution formulation. Thus, the PLA nanoparticles were unable to increase the zidovudine bioavailability compared to aqueous solution formulation. The results obtained in this study indicate the potential of the PLA-PEG blend nanoparticles as carriers for zidovudine delivery by the intranasal route. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Nanoparticles; Intranasal administration; Zidovudine; Bioavailability